UYSD: a novel data repository accessible via public website for worldwide population frequencies of Y-SNP haplogroups - Ralf, Arwin; Zandstra, Dion; van Wersch, Bram; Köksal, Zehra; Larmuseau, Maarten H D; Rosa, Alexandra; Jobling, Mark A; D'Amato, Maria E; Courts, Cornelius; Gysi, Mario; Haas, Cordula; Flores, Rodrigo; et al. (European journal of human genetics, 2025)
For decades, there has been scientific interest in the variation and geographic distribution of paternal lineages associated with the human Y chromosome. However, the relevant data have been dispersed across numerous publications, making it difficult to consolidate. Additionally, understanding the relationships between different variants, and the tools used to analyze them, have evolved over time, further complicating efforts to harmonize this information. The Universal Y-SNP Database (UYSD) marks a substantial advancement by providing a comprehensive and accessible platform for Y-SNP and haplogroup data from populations around the world. UYSD harmonizes diverse datasets into a unified repository, facilitating the exploration of global Y-chromosomal variation. The platform handles data generated with both high- and low-throughput technology and is compatible with the automated analysis software tool, Yleaf v3. Key functionalities include the ability to: i) visualize haplogroup distributions on an interactive world map, ii) estimate haplogroup frequencies in geographic regions with sparse data through interpolation, and iii) display detailed phylogenetic trees of Y-chromosomal haplogroups. Currently, UYSD encompasses data from over 6,600 males across 27 populations. This dataset largely aligns with known global Y-haplogroup patterns, but also reveals unexplored finer-scale geographic variations. While the present dataset is largely European-centered, UYSD is designed for ongoing expansion by the scientific community, aiming to include more global data and higher-resolution population sequencing data. The platform thus offers valuable insights into human genetic diversity and migration patterns, serving several fields of research such as: human population genetics, genetic anthropology, ancient DNA analysis and forensic genetics.
Keywords: Genetics, Population; Databases, Genetic; Software; lidský chromozom Y; jednonukleotidový polymorfismus; software; Polymorphism, Single Nucleotide; Haplotypes; haplotypy; Humans; mužské pohlaví; Male; lidé; databáze genetické; populační genetika; Chromosomes, Human, Y; fylogeneze; Phylogeny